EFL teachers’ maxims: the impact of COVID-19 pandemic on online teaching in the Thai tertiary context - Thitirat Suwannasom, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The COVID-19 pandemic in Thailand in 2020-2021 tremendously affected English language instruction in higher education institutions. When most English as a Foreign Language (EFL) teachers had to relocate their classes from face-to-face settings to online platforms, they were required to change their instructional techniques, tools and materials, and class activities to cope with the new classroom environment. This study aimed to examine English teachers' maxims of teaching the English language through online applications during the COVID-19 pandemic in 2020-2021, which intensified the technology disruption in teaching. The main objective was to investigate teachers' personal principles regarding online instruction and emerging challenges. The quantitative data was obtained by a survey questionnaire administered to 67 university EFL lecturers. The qualitative data was collected through personal narratives and focus group interviews with 12 volunteer lecturers who shared their personal principles that navigated their teaching approaches. The findings revealed that the emerging teachers' maxims in online learning included planning lessons and selecting instructional tools, facilitating students' engagement, maintaining class management and order, and interacting with peer teachers. It was found that the major challenges in EFL online instruction were the effectiveness of instruction and issues in promoting students’ engagement in collaborative tasks. In addition, the pivotal factors influencing virtual classrooms included teachers’ level of preparation and students’ limited interactions.